Accessing asylum in Europe : extraterritorial border controls and refugee rights under EU law - Moreno Lax, Violeta (Oxford : Oxford University Press, 2017)
The timely subject matter of this work focuses on the interface between extraterritorial border surveillance and migration control by EU member states, and the rights that asylum seekers acquire from EU law. In particular Moreno-Lax concentrates on the relationship between the EU Charter of Fundamental Rights and border control measures.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 15, 2017).
Keywords: Asylum, Right of -- European Union countries; Border security -- European Union countries; Political refugees -- Legal status, laws, etc. -- European Union countries; Law; Laws of specific jurisdictions & specific areas of law